Autodiagnóstico para inserção do marketing digital nas micro e pequenas empresas varejistas - Silva, Gizele Catarina Martins da (2023)
Digital marketing is a strategic resource capable of adding value to consumers, training new customers, maintaining the customer network, expanding companies, meeting the needs of the market and customers, learning about new suppliers, among other possibilities. In this context, the creation of a self-diagnosis instrument for the insertion of Digital Marketing in Micro and Small Companies (MSEs) in the retail segment is an impetus for these companies to take advantage of digital media platforms to increase their visibility, reach, sales opportunities and approximation to potential customers. Thus, the present study aims to develop a self-diagnosis for the insertion of digital marketing in the strategies of Micro and Small Enterprises (MSEs) in the retail trade segment. The study is carried out within the framework of applied research, which aims to generate knowledge for practical application aimed at solving specific problems. As a result, a self-diagnosis instrument for EPM and an action plan were proposed. The selfdiagnosis can be accessed online by the entrepreneur, from a mobile device, and was organized into three dimensions: the first, consisting of three questions, which synthetically identifies the company's organizational model; the second, which identifies how the company relates to consumers and the market in which it operates; and the last dimension, which corresponds to the analysis of the company in the virtual environment. Based on the results obtained with the responses, an action plan is made available to the company. The self-diagnosis evaluation was carried out through an opinion poll with ten MSEs obtaining positive results.